2020
DOI: 10.1259/bjr.20190250
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiologically derived biphasic fractionation schemes to overcome the effects of tumour hypoxia

Abstract: Objective: As a fractionated course of radiotherapy proceeds tumour shrinkage leads to resolution of hypoxia and the initiation of accelerated proliferation of radioresistant cancer cells with better repair capacity. We hypothesise that, in tumours with significant hypoxia, improved tumour control could be achieved with biphasic fractionation schedules that either use acceleration after 3–4 weeks of conventional radiotherapy or deliver a higher proportional dose towards the end of a course of treatment. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…With the close relationship between hypoxia and fractionation in mind, 35 , 36 , 37 we hypothesised that either a delayed acceleration fractionation or temporal fractionation schedule could account for hypoxia in tumours and take advantage of progressive reoxygenation in the first few weeks of treatment. 33 There is little clinical evidence for this effect as data sets for hypoxic tumours with different fractionation schedules are rare.…”
Section: Discussionmentioning
confidence: 99%
“…With the close relationship between hypoxia and fractionation in mind, 35 , 36 , 37 we hypothesised that either a delayed acceleration fractionation or temporal fractionation schedule could account for hypoxia in tumours and take advantage of progressive reoxygenation in the first few weeks of treatment. 33 There is little clinical evidence for this effect as data sets for hypoxic tumours with different fractionation schedules are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have con rmed that tumor cells can accelerate re-proliferation after irradiation, which is manifested by prolonged treatment time and adecreased local control rate of tumor [7,8]. Koukourarkis and Hlouverakis et al [9] found a 25-40% decrease in tumor-free survival with a 14-day extension of the tumor treatment course.…”
Section: Introductionmentioning
confidence: 99%